Development of a design for an ionisation vacuum gauge suitable as a reference standard. (January 2021) - Jenninger, Berthold; Anderson, Johan; Bernien, Matthias; Bundaleski, Nenad; Dimitrova, Hristiyana; Granovskij, Mihail; Illgen, Claus; Setina, Janez; Jousten, Karl; Kucharski, Pawel; Reinhardt, Christian; Scuderi, Francesco; et al.
Abstract: The EURAMET EMPIR project "16NRM05 - Ion gauge" aims to develop an ionisation vacuum gauge suitable as a reference vacuum standard. In such a gauge the electron trajectories and their kinetic energy inside the ionisation volume should be well defined and stable. In the search for a suitable design, a series of simulations on different ionisation gauge concepts that have the potential to meet stringent stability requirements have been carried out. Different software packages were used for this purpose. This paper focuses on the design aspects and the performance of the different ionisation gauge concepts that have been investigated by simulation. Parameters such as ionisation gauge sensitivity, ion collection efficiency and electron transmission efficiency, have been determined as a function of emission current, pressure and electron source alignment. Highlights: A new type of ionisation vacuum gauge with predictable sensitivity is proposed. Simulations of ion and electron trajectories make development of new ion gauge very efficient. Results of simulations and first measurements agree well.